A Metacognitive-Attributional Approach to Tutoring Student-Athletes: Putting Theory into Practice at UNLV - Elrod, G. Franklin (My University, 1985)
The following article offers a psycho-educational approach to tutoring high risk collegiate student-athletes. A four component approach is detailed. The four components are: 1) a metacognitive reading process, 2) a relationship of this process to athletics, 3) an attributional component to assist in motivation, and 4) a cognitive problem solving component that can be used on a personal computer. When appropriate, the various components are supported by relevant research. A discussion section summarizes the application of each component and suggests areas where further research is needed.
Keywords: academic support; basketball; Division I; skills